The Influence of Audiovisual-Based Education on Knowledge and Attitudes About Bullying Prevention in Children at State Elementary School No. 4 Tanjung Batu - Evidamayanti Evidamayanti; Ahmad Mawardi; Wilna Sari Sumiati; Nurwahita Nurwahita (Jurnal Ners, 2026)
Audiovisual-based education is a form of intervention that provides information and understanding to enhance an individual's knowledge and skills by using media that combines sound and visual elements. The implementation of audiovisual-based education on bullying prevention at State Elementary School No. 4 Tanjung Batu is categorized as good. This research was conducted to determine whether there is an influence of audiovisual-based education on the knowledge and attitudes about bullying prevention in children at State Elementary School No. 4 Tanjung Batu. This research is a quantitative study with a quasi-experimental design using a one-group pretest and posttest design. The sample consisted of 40 individuals using a total sampling technique. The research instruments used for the knowledge and attitude variables were questionnaires. The collected data were processed and then analyzed using univariate frequency and bivariate Wilcoxon tests. The obtained p-value was 0.000, and since p < 0.05, Ha was accepted, indicating that there is an influence of audiovisual-based education on the knowledge and attitudes about bullying prevention in children at State Elementary School No. 4 Tanjung Batu.